2009
DOI: 10.1071/cp08357
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and persistence of perennial grass and herb cultivars and lines in a recharge area, North-West Slopes, New South Wales

Abstract: Two adjacent sites, one previously cropped and the other a native pasture, were sown with perennial temperate and tropical grasses and herbs (Expt 1), Phalaris aquatica (phalaris) and Festuca arundinacea (tall fescue) cultivars or lines (Expt 2), and perennial tropical grasses (Expt 3) near Manilla, NSW. Establishment, herbage mass and plant frequency were assessed in 2003–06 to (i) identify cultivars/lines with superior persistence, (ii) detect possible mechanisms required for successful production and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Both perennial grasses have shown wide adaptation and high production (e.g. McCormick et al ., ; Boschma et al ., ) and forage sorghum is the commonly sown summer forage in this environment. The perennial grasses were sown with a tyned cone seeder (six rows, 0·2 m apart) on 6 December 2005 to a depth of 5 mm at 2 kg ha −1 viable seed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both perennial grasses have shown wide adaptation and high production (e.g. McCormick et al ., ; Boschma et al ., ) and forage sorghum is the commonly sown summer forage in this environment. The perennial grasses were sown with a tyned cone seeder (six rows, 0·2 m apart) on 6 December 2005 to a depth of 5 mm at 2 kg ha −1 viable seed.…”
Section: Methodsmentioning
confidence: 99%
“…During 2003–06, Boschma et al . () evaluated a range of temperate and tropical grasses as part of a national evaluation programme (Nie et al ., ; Reed et al ., ). These studies were conducted during an extended period of low rainfall and clearly showed the contrasting production potential and responsiveness to rainfall of tropical grasses compared to temperate grasses.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The results from the current study are complemented by those from later studies of mostly perennial legumes reported by Li et al (2008), Boschma et al (2010a) and Boschma et al (2011) for a site on a Brown Vertosol soil, near Manilla on the North-West Slopes of NSW, which included entries of sulla, Onobrychis viciafolia Scop. (sainfoin) and lucerne.…”
Section: Discussionmentioning
confidence: 56%